Pengaruh Perilaku Kepemimpinan Terhadap Motivasi Kerja Pegawai Pada Kantor Desa Abbanuangnge Kecamatan Maniangpajo Kabupaten Wajo - Darwis Darwis; Najeminur Najeminur; Andi Supriadi (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This research was motivated by preliminary research at the Abbanuangnge Village Office, Maniangpajo District, Wajo Regency, with initial information that could be obtained, namely the impression that the work motivation of employees at the Office, a number of ideals were thought to be influenced by leadership behavior which was also not ideal. This research aims to examine the influence of leadership behavior on employee work motivation at the Abbanuangnge Village Office, Maniangpajo District, Wajo Regency. This research uses quantitative research methods. The population in this study was all 8 Abbanuangnge Village Office employees. The sample in this research uses a saturated sample, namely a sampling technique when all members of the population are used as samples. The primary data source is in the form of a questionnaire. The data analysis techniques used are descriptive statistical analysis, correlation analysis, coefficient of determination, simple linear regression. The questionnaire measurements answered by respondents used a Likert scale which was processed using the Statistical Product and Service Solution (SPSS). The results of this research show that training has a positive and significant influence on the performance of civil servants at the Pammana District Office, Wajo Regency. Meanwhile, the R2 (R Square) value is 0.623, which shows that the percentage contribution of the Training variable to the Civil Servant Performance variable at the Pammana District Office, Wajo Regency is 62.3%.